2002
DOI: 10.1111/j.1749-6632.2002.tb04191.x
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant μ‐δ Receptor as a Marker of Opiate Abuse

Abstract: The brain is particularly vulnerable to drugs of abuse changing the neuroreceptor functions. Opiates interact and overstimulate heterogeneous opioid receptors leading to their desensitization, internalization, and activation of recombinant opioid receptor. The molecular properties of rat and human brain recombinant μ‐δ receptor were compared with those of purified μ‐ and δ‐receptors. cDNA coding the unique fragment of recombinant μ‐δ receptor was isolated and sequenced. We hypothesized that recombinant μ‐δ rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…An elevation of circulating aAbs directed against MDOR and GluR1 receptors was recently demonstrated in human opiate addicts (Dambinova and Izykenova 2002) and in morphine-treated rats (Granstrem et al 2006). Here, we describe specific neurobehavioral alterations associated with an elevation of circulating aAbs in mice immunized with these two selected neuroreceptor fragments.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…An elevation of circulating aAbs directed against MDOR and GluR1 receptors was recently demonstrated in human opiate addicts (Dambinova and Izykenova 2002) and in morphine-treated rats (Granstrem et al 2006). Here, we describe specific neurobehavioral alterations associated with an elevation of circulating aAbs in mice immunized with these two selected neuroreceptor fragments.…”
Section: Resultsmentioning
confidence: 97%
“…It has recently been shown that μ-δ interacting complexes exist and that occupancy of δ receptors is sufficient to enhance μ receptor binding and signaling activity (Gomes et al 2000(Gomes et al , 2004Bailey and Connor 2005). In a previous study, Dambinova and Izykenova (2002) used a recombinant MDOR fragment as antigen to demonstrate the presence of aAbs to MDOR in the blood of rats trained to self-administer heroin as well as in human drug abusers. The same fragment was used as an immunogen in the present study.…”
Section: Mdor Immunizationmentioning
confidence: 98%
“…Such observations support the hypothesis that, opiates could be common mediators between the nervous and the immune system. The high levels of aAbs to MDOR were also observed in heroin selfadministering rats as well as in human addicts and shown as a function of severity of opiate addiction (Dambinova and Izykenova, 2002), suggesting that opiate addiction may be somehow associated with autoimmune response/processes. Koziol and collègues (1997) compared the range of ANA in "healthy" individuals in comparison with patients with autoimmune disorders such as systemic lupus erythematosus, systemic sclerosis, sjogren's syndrome and rheumatoid arthritis, or soft tissue rheumatism.…”
Section: Auto-antibodies In Individuals With Different Mor Allelesmentioning
confidence: 87%
“…Only a few studies have attempted to determine factors that connect opiate use with the development of autoimmune processes. Several authors have suggested that administration of an opiate agent was associated with elevated levels of autoantibodies to mu delta-opiate receptors (MDORs) in non-drug users as well as in heroin addicts [ 58 , 59 ].…”
Section: The Role Of the Opioid System In Hemato-oncological Conditiomentioning
confidence: 99%